Nudging Commuters to Increase Public Transport Use: A Field Experiment in Rotterdam - Franssens, Samuel; Botchway, Ebo; de Swart, Willie; Dewitte, Siegfried (Frontiers in Psychology, 2021)
A large-scale field experiment in Rotterdam, The Netherlands, tested whether nudging could increase public transport use. During one work week, 4000 commuters on six bus lines, received a free travel card holder. On the three bus lines in the experimental condition, the card holders displayed a social label that branded bus passengers as sustainable travelers because of their bus use. On the three bus lines in the control condition, there was no such message on the card holders. Analysis of the number of rides per hour showed that the intervention led to a change from pre-intervention (619 days) to post-intervention period (176 days) that was estimated to be 1.18 rides per day greater on experimental lines than on control lines. This experiment shows that public transport operators can increase public transport use by incorporating messages that positively label passengers as sustainable travelers in their communication strategies.